Regional Economic Outlook, May 2008, Middle East and Central Asia. (Regional Economic Outlook, 2008)
The Middle East and Central Asia region grew at 6.5 percent in 2007, marking its best five-year performance over the past 30 years. So far, the turmoil in international financial markets has had a limited impact on the region, and the short-term outlook remains very favorable. The report reviews recent economic developments, assesses the outlook for the coming year, and discusses key policy challenges. In addition, it takes a closer look at both regional topics--such as the rise in inflation in the GCC countries, intraregional capital flows, developments in oil markets, developments in real estate prices, and sovereign wealth funds--and country reviews for Algeria, Georgia, Iraq, and West Bank and Gaza.